Growth and Yields Response of Some Varieties of Soybean (Glycine Max (L) Merill) on Ultisol Soil - Tambunan, Syariani; Afkar, Afkar; Sebayang, Nico Syahputra (Indonesian Journal of Agricultural Research, 2019)
Soybean is an agricultural product that has a good nutritional value, especially Protein content. This study aims to find superior varieties that have a wide adaptation to the sour soil especially in Ultisol soils. The study was conducted in Gulo Village, Darul Hasanah Sub-District, Southeast Aceh Regency, Aceh Province, from May to September 2019. The study used a non factorial randomized block design (RBD), with 4 treatment varieties (V) levels that were repeated as many as 4 replications; namely V1: Anjasmoro Varieties, V2: Dena Varieties, V3: Deja Varieties 1, V4: Detaptive Varieties 1, Variance analysis test results showed that the plant height was 1 WAP, Age 2 WAP, Age 3 WAP, Age 4 WAP, Age 5 WAP , and Age 6 WAP had no significant effect. However the highest yield on 1 WAP was found in variety V4 (10.40) in the second test and the lowest was in the first test. V2 was second test. While the best number of segments and branches were produced by V3 treatment. The best results for the total number of pods, number of pods, total empty pods, number of sample plant seeds and weight of sample plant seeds were produced by treatment V3.